Utilisation of Demographic Bonus through Securities Crowdfunding Mediated by Financial Literacy, Inclusion and Trust - Naufalia, Viani (Otoritas Jasa Keuangan, 2024)
The threat of the middle-income trap can actually be countered by Indonesia by exploiting and optimising demographic bonus, one of which is by maximising the potential of MSMEs as the largest contributor to national economic growth, namely by providing an alternative financing of Securities Crowdfunding listed in rule No. 16/POJK.04/2021. However, if we look at the demographic bonus conditions in Indonesia, we can see the negative gaps of the demographical bonus conditions, namely the lack of literacy, inclusion, and trust of MSMEs players in digital finance. So, the aim of this research is to find out how the exploitation of demographic bonus can be optimised through the innovation of securities crowdfunding, as well as supported by the mediation variables of financial literacy, inclusion and trust. The researchers used a quantitative research method with primary data in the form of a survey of 393 respondents from MSMEs in DKI Jakarta and its surroundings who are aged 15-49 years, then data analysis technique is Structural Equation Modelling (SEM) with the application SMART PLS 4.0. The results of this study show that securities crowdfunding can optimise the demographic bonus of 76.9%, then the conditions of financial literacy and inclusion can also support the implementation of securities crowdfunding in optimising demographic bonus of 61.2% and 59.7%. Thus, it is expected that the future potential of these securities crowdfunding can really be optimised to be one of the solutions for growing the national economy in the era of demographic bonus. In addition, the research also has implications for several sectors, as well as producing some policy recommendations.